2019
DOI: 10.1002/chem.201901237
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Photochemical [2+2] Cycloaddition Reaction of MnII Complexes

Abstract: Three Mn II complexes have been synthesized under similare xperimental conditions. Of these [Mn 2 (benzoate) 4 (L) 2 ]( whereL = 4-styrylpyridine or 4spy, 1 and 2-fluoro-4'-styrylpyridineo r2 F-4spy, 3)a re paddlewheel complexes, but crystallized in different space groups.W hereas [Mn 2 (benzoate) 4 (3F-4spy) 4 ]( 3F-4spy = 3-fluoro-4'-styrylpyridine), 4 is ad inuclearc omplex having different stoichiometry from 1 and 3 with two pairs of 3F-4spy ligandsalignedi n face-to-face manner.A ni rreversible phase tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As for the olefin-based molecular crystals, [2 + 2] cycloaddition between adjacent C�C double bonds would trigger the macroscopic mechanical motions. Although styrylpyridine is one of the widely studied building blocks in photomechanical systems, 23,24 the distance between adjacent C�C double bonds was often greater than 4.2 Å in crystals. 20,25 Accordingly, the template-assisted method has been employed for the prearrangement of styrylpyridine units in crystals so as to make the packing meet Schmidt's criteria.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the olefin-based molecular crystals, [2 + 2] cycloaddition between adjacent C�C double bonds would trigger the macroscopic mechanical motions. Although styrylpyridine is one of the widely studied building blocks in photomechanical systems, 23,24 the distance between adjacent C�C double bonds was often greater than 4.2 Å in crystals. 20,25 Accordingly, the template-assisted method has been employed for the prearrangement of styrylpyridine units in crystals so as to make the packing meet Schmidt's criteria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As for the olefin-based molecular crystals, [2 + 2] cycloaddition between adjacent CC double bonds would trigger the macroscopic mechanical motions. Although styrylpyridine is one of the widely studied building blocks in photomechanical systems, , the distance between adjacent CC double bonds was often greater than 4.2 Å in crystals. , Accordingly, the template-assisted method has been employed for the prearrangement of styrylpyridine units in crystals so as to make the packing meet Schmidt’s criteria. , Vittal and Rath presented the photosalient behavior of the crystal based on the complexes where the distorted octahedral Pb­(II) center is coordinated to the N atom in styrylpyridine derivatives and the strain is generated during the photo-induced [2 + 2] cycloaddition reaction. , MacGillivray et al reported the supramolecular alignment between resorcinol and styrylpyridine via multiple H-bonds of O–H···N so as to realize the photochemical reaction-powered mechanical response of the crystals . Besides, much effort is also made to optimize the olefin geometry, such as cocrystal engineering.…”
Section: Introductionmentioning
confidence: 99%
“…S8, ESI †). 28,37,38 To get better insight into the photomechanical behavior, the faces of the single crystal of 1 have been indexed. It can be noticed that the (110) plane is cleaved in the crystal under UV light, which indicates that [Zn 2 (CO 2 ) 4 ] dimers that propagate along the a-axis are disrupted.…”
mentioning
confidence: 99%
“…Coordination polymers offer some advantages in this respect, including better thermal stability and the potential for multi-stimuli behaviours related to redox reactions of the metal centres. 1,6,7,[24][25][26] The photosalient (PS) properties 12 arising from a [2+2] cycloaddition reaction are mainly due to the strain energy accumulated during the rapid structural transformation. 9,24,27 This release of energy over a relatively short period of time often results in crystal disintegration.…”
mentioning
confidence: 99%
“…Coordination polymers offer some advantages in this respect, including better thermal stability and the potential for multi-stimuli behaviours related to redox reactions of the metal centres. 1,6,7,24–26…”
mentioning
confidence: 99%